DEVELOPMENT OF THE METHOD OF CLASSIFICATION OF FUNCTIONAL FAILURES OF RADIO ELECTRONIC NAVIGATION SYSTEMS BASED ON THE THEORY OF FUZZY SETS - Rahulin, S. V. (Systems and Technologies, 2025)
The continuous increase in the complexity of radio electronic navigation systems of aircraft and the expansion of the circle of their functions have led to the fact that in order to manage the technical condition of radio electronic navigation systems, enterprises that operate forced to perform a considerable amount of work on maintenance and repair. The operating costs for maintenance and repair of radio electronic navigation systems are currently reaching 30-40% of the total cost of maintenance and repair of aircraft [1]. Therefore, it is urgent to increase the efficiency of the maintenance and repair system by reducing operating costs while maintaining flight shelf life and competitiveness of aircraft.The work defines the criteria for optimizing the technical support of radio electronic navigation systems on the basis of substantiation of the possibility of using various technical and technical and economic indicators of efficiency of operation, classification of radio electronic navigation systems on the grounds that take into account the specific features of their use by purpose. Classification of possible variants of strategies for maintenance and repair of radio electronic navigation systems, which differ in the level of diagnostic support and place of restoration of blocks and modules. For the correct approach to optimization of the exchange fund, there is a classification of options for constructing the inventory management system and a determined number of storage levels of inventory. According to the types of special situations established by the standards of flight suitability, radio – electronic navigation systems were classified by the degree of influence of functional refusals on the safety of air courts. The classification was developed based on the probability assessment of functional failures in flight in the presence of information on reliability of radio electronic navigation systems. For the absence of statistics to calculate probabilistic indicators, the method of classification of radio electronic navigation systems was developed based on a logical-linguistic approach using fuzzy set theory.